Realization of 1 μm thick, crack-free and smooth PMN-PT film in the MPB through PLD: A comprehensive study. Issue 17 (1st December 2020) - Augustine, Pius; Rath, Martando; Haripriya, G.R.; Sethupahi, K.; Rao, M. S. Ramachandra
Abstract: This paper presents a comprehensive study on the various hurdles and solutions in the realization of phase pure, pinhole-free and crack-free, 0.65PMN-0.35PT/LSCO/Pt/TiO2 /SiO2 /Si heterostructures using pulsed laser deposition. A few major inquiries were i) effect of excess PbO in the target, ii) modulation of deposition and annealing temperatures for the growth of LSCO buffer layer, iii) thickness of the buffer layer iv) effect of the flow of oxygen in the chamber during and after deposition and v) the annealing conditions; on the phase formation, morphology and leakage response demonstrated by the films. Ferroelectric response parameters viz. Psat  = 47.7 μC/cm 2, Pr  = 20.03 μC/cm 2, EC  = 62.03 kV/cm and absolute area = 21460 units attest the quality of the grown film. Graphical abstract: Image 1